2015
DOI: 10.1177/0891242415614641
|View full text |Cite
|
Sign up to set email alerts
|

Do Incentive Programs Cause Growth? The Case of the Oklahoma Quality Jobs Program and Community-Level Economic Growth

Abstract: The academic literature on economic development incentive programs has generated mixed results, though most studies conclude that incentives do not lead to economic growth. Oklahoma has received high praise for its innovative Quality Jobs program, because it provides cash payments (not tax incentives) and emphasizes jobs with high wages and benefits. However, few evaluations of the program’s success in growing the state’s economy have been made. This study employs multivariate regression and mixed-pair analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…At the same time, states and cities competed fiercely for business in the name of economic development policy. The -2009 Great Recession was in part blamed for tightened public support for higher education; by contrast, it led to increased reliance on incentive programmes for job creation and retention by state and local governments (Osgood et al 2012;Whitacre et al 2016). The New York Times reported that state and local governments spent $80 billion a year for business incentives (Story 2012), which is equivalent or even more than state support for public higher education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, states and cities competed fiercely for business in the name of economic development policy. The -2009 Great Recession was in part blamed for tightened public support for higher education; by contrast, it led to increased reliance on incentive programmes for job creation and retention by state and local governments (Osgood et al 2012;Whitacre et al 2016). The New York Times reported that state and local governments spent $80 billion a year for business incentives (Story 2012), which is equivalent or even more than state support for public higher education.…”
Section: Introductionmentioning
confidence: 99%
“…Given the associated budget constraint, it was no surprise to see state education budget cuts following large big business incentives in the state of Kansas (Story 2012). As reviewed by Whitacre et al (2016), however, most recent research has found little or no impact of business incentive programmes on economic growth. Thus it is reasonable to question the practices of state governments that increase economic development incentives at the expense of dwindling support for higher education, even simply in the context of economic development.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research has documented the positive influence of the B&I (or similar) programs on employment or wages Whitacre et al, 2016), but few evaluations have assessed impacts to local tax revenues. Although influencing these revenues is not listed in the mission statement or goals of USDA RD, we argue that such funds are vital for city governments to maintain and improve their residents' quality of life, and that the concept of "tax adequacy" should be more mainstream in the community development discourse.…”
Section: Resultsmentioning
confidence: 99%
“…One study of a non-USDA economic development program is Whitacre, Shideler, and Williams' (2016) evaluation of Oklahoma's Quality Jobs program, which also used multivariate regression and matching approaches. The results revealed no evidence that Oklahoma communities participating in the Quality Jobs program had economic growth compared to Oklahoma communities not participating the in program (Whitacre et al, 2016). However, when comparing Oklahoma communities participating in the program to Kansas communities (where no Quality Jobs program exists) there was statistical evidence of median household income growth (Whitacre et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 85%
See 1 more Smart Citation